Civil participation in sustainable development of single-industry towns - N. N. Golivtsova (Путеводитель предпринимателя, 2020)
Among the most urgent trends that characterize the development processes of many regions, its significance in the socio-economic impact highlighted the growing contrasts of municipalities within them. The article analyzes the existing approaches to definition of concept «monocity». The authors defined the Russian specificity of «towns». The analysis of characteristics of single-industry towns of the North-Western Federal district by categories. Directions of support the development of «company towns» on the basis of broad public participation in development management.